Penindasan Perempuan dalam Film Andai Ibu Tidak Menikah Dengan Ayah Karya Evelyn Afnilia: Kajian Feminisme Radikal - Nabila Nur Aulia; Baiq Nurmarini Nursaly; Mudarman (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2026)
This study aims to describe the forms of oppression against women and the impact of such oppression on psychosocial conditions in the film Andai Ibu Tidak Menikah dengan Ayahb by Evelyn Afnilia, based on Kate Millett’s radical feminist perspective. The research method used is qualitative descriptive, employing a literature review approach. Data collection was conducted through observation and note-taking combined with documentation to deepen the analysis of the film’s content. The theoretical framework employed is Kate Millett’s radical feminism, which views patriarchal culture as the root of women’s oppression, positioning men as the dominant group holding full power and rights, while women are positioned as the disadvantaged group. The research data consisted of scene excerpts, dialogue, and character expressions. The data were analyzed using the Miles and Huberman model, which includes data reduction, data analysis, data presentation, and drawing conclusions. The results of the study indicate that several forms of women’s oppression are represented in the film, namely labeling, marginalization, subordination, and the double burden. This oppression impacts the psychosocial condition of the female characters, manifesting as emotional stress, disappointment, frustration, mental exhaustion, limitations in making life choices, and the loss of opportunities for women to develop their full potential. From the perspective of Kate Millett’s radical feminism, this film demonstrates that patriarchy not only creates social inequality but also influences psychosocial conditions through control and the domination of power within family life.